Bilateral internal mammary artery grafting in diabetics: Outcomes, concerns and controversies. (April 2015) - Raja, Shahzad G.
Abstract: Coronary artery disease (CAD) is a leading cause of mortality and morbidity in diabetics. Diabetics make up to 20%–35% of all patients undergoing coronary revascularization. Patients with diabetes represent a particularly difficult subset for revascularization due to increased short- and long-term mortality as well as a higher risk of repeat revascularization procedures. Potential factors contributing to the increased risk include co-morbid illnesses, small, diffusely diseased target vessels, progression of native CAD, hyperglycaemic endothelial dysfunction, and systemic inflammation. For diabetic patients with multi-vessel disease, revascularization by coronary artery bypass grafting (CABG) is regarded as the preferred option. There is increasing recognition that the use of arterial conduits for CABG is associated with improved outcomes compared to use of venous conduits. Amongst arterial conduits bilateral internal mammary arteries (BIMA) have emerged as the superior conduits due to better cardiac event-free survival. Consistent with its benefits in non-diabetic patients, BIMA grafting is presumed to offer similar benefits in diabetic patients. However, BIMA grafting remains underutilised in diabetics due to perceived increased risk of sternal wound infection. This review article provides an overview of BIMA grafting in diabetic patients focussing on outcomes, concerns, and controversies associated with BIMA usage in this high-risk group of patients. Highlights: Coronary artery disease is a leading cause of mortality and morbidity in diabetics. Coronary artery bypass grafting is the preferred option for diabetics. BIMA grafting is a superior form of surgical revascularization. Diabetics are less frequently offered BIMA grafting. Reported outcomes of BIMA grafting in diabetics are encouraging.